2016
DOI: 10.2106/jbjs.cc.15.00271
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Hip Fracture-Dislocation: Transphyseal Fracture with Posterior Dislocation of the Proximal Femoral Epiphysis

Abstract: Traumatic transepiphyseal fracture-dislocations are rare injuries that commonly result in osteonecrosis. Application of the Ganz surgical hip-dislocation technique to a difficult pediatric hip fracture-dislocation achieved an excellent result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Van Nortwick et al performed a Ganz osteotomy to repair a posterior transphyseal SH III hip fracture-dislocation in a thirteen-year-old male; he had no osteonecrosis or functional limitations at two-year follow-up [ 11 ]. Mehlman et al found that delaying reduction over six hours increased the risk of AVN twenty-fold, and the only factor correlating with development of AVN was length of time between injury and relocation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Van Nortwick et al performed a Ganz osteotomy to repair a posterior transphyseal SH III hip fracture-dislocation in a thirteen-year-old male; he had no osteonecrosis or functional limitations at two-year follow-up [ 11 ]. Mehlman et al found that delaying reduction over six hours increased the risk of AVN twenty-fold, and the only factor correlating with development of AVN was length of time between injury and relocation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%